2008
DOI: 10.1088/0022-3727/41/2/025403
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical modelling of the direct metal deposition laser process

Abstract: The direct metal deposition (DMD) laser process is a novel technique, well adapted for aeronautical applications, that allows the building of complex 3D geometries through the interaction between a powder nozzle system and a continuous laser beam. A three-step analytical and numerical approach was carried out to predict the shapes of manufactured structures and thermal loadings induced by the DMD process. First, powder temperature was calculated using a recent analytical model, then the geometry of walls was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(136 citation statements)
references
References 12 publications
5
129
0
2
Order By: Relevance
“…Such an absorption coefficient is in the same order of magnitude (around 0.3) but a little higher than what has been previously found in anterior work. 16 When compared with experimental data, it was confirmed that numerical results (Table II, Fig. 8), provided a correct estimation of layer heights and melt-pool dimensions (MP), despite a slight overestimation (þ10%) of MP height and length by the numerical model as shown in the histograms of Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Such an absorption coefficient is in the same order of magnitude (around 0.3) but a little higher than what has been previously found in anterior work. 16 When compared with experimental data, it was confirmed that numerical results (Table II, Fig. 8), provided a correct estimation of layer heights and melt-pool dimensions (MP), despite a slight overestimation (þ10%) of MP height and length by the numerical model as shown in the histograms of Fig.…”
Section: Resultssupporting
confidence: 64%
“…11,12 Last, recent modeling like those by Mirzade 13 have considered undercooling during crystallization as a possible modification of melt zone contours whereas Suarez et al In our recent work, different FE models were proposed, starting from rather simple solid simulations considering layer growth through the x-displacement of a thermal conductivity front (Heaviside step function) 16 on predefined layers. The main drawback of this model was the heat source positioning (on the top of planar additive layers) which was not fully representative of the real laser absorption on an inclined shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This periodicity, as well as the truncated cellular structures shown in Figure 3((a), (a-3)), indicates that a Mullins and Sekerka instability [33,34] is operating with a characteristic wavelength of *Laser absorption based on experimental results from other authors. [43] ~7 lm. Of note, the Mullins and Sekerka can be established by small perturbations in the solid-liquid interface, or in the thermal fields that arise from very localized turbulence at the solid/liquid interface.…”
Section: A As-deposited Microstructure: Effect Of W On Local Chemistrymentioning
confidence: 99%
“…Thus, the powder interacts strongly with the the fluid dynamics of the shielding gas, that effects crucially the trajectory of single powder particles and hence, its location of deposition. Numerical approaches developed by He et al [2], Peyre et al [3], Wen et al [4] and Qi et al [5] describe the fusion process, however, neglect the transport of powder between nozzles and substrate. Therefore, the objective of the current contribution is to describe numerically the complex process of powder deposition on a substrate.…”
Section: Introductionmentioning
confidence: 99%